2019
DOI: 10.7150/thno.36605
|View full text |Cite
|
Sign up to set email alerts
|

miR-302a Inhibits Metastasis and Cetuximab Resistance in Colorectal Cancer by Targeting NFIB and CD44

Abstract: Introduction: Metastasis and drug resistance contribute substantially to the poor prognosis of colorectal cancer (CRC) patients. However, the epigenetic regulatory mechanisms by which CRC develops metastatic and drug-resistant characteristics remain unclear. This study aimed to investigate the role of miR-302a in the metastasis and molecular-targeted drug resistance of CRC and elucidate the underlying molecular mechanisms.Methods: miR-302a expression in CRC cell lines and patient tissue microarrays was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 49 publications
1
43
0
Order By: Relevance
“…NFIB appeared in all four databases and has been reported as a target gene of miR-346 in glioma [32]. Moreover, NFIB was identified as an oncogene in CRC [31,43]. THPA database and qRT-PCR experiment both demonstrated that NFIB was upregulated in CRC.…”
Section: Discussionmentioning
confidence: 98%
“…NFIB appeared in all four databases and has been reported as a target gene of miR-346 in glioma [32]. Moreover, NFIB was identified as an oncogene in CRC [31,43]. THPA database and qRT-PCR experiment both demonstrated that NFIB was upregulated in CRC.…”
Section: Discussionmentioning
confidence: 98%
“…However, most CRCs are either inherently insensitive to therapeutic treatment or acquire resistance upon relapse 3 . There is a critical need for developing novel and more effective CRC therapies, especially for those with intrinsic or acquired resistance to existing treatments 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effects of miR-302a-3p are mediated via the MAPK and PI3K/Akt signalling pathways [ 160 ]. The tumour suppressor role of miR-302a-3p is also executed by targeting nuclear factor IB ( NFIB ) and the induction of cetuximab chemosensitivity, which is caused by suppressing cell-surface expression of the glycoprotein CD44 [ 161 ]. miR-302a-3p also induces 5FU sensitivity and viability inhibition via the inhibition of IGF1R [ 162 ].…”
Section: Mirna Clusters Down-regulated In Human Crcmentioning
confidence: 99%